Notes on some Tanzanian butterfly specimens in the Suffert Collection: a case of patria falsa - Takano, Hitoshi; László, Gyula M.; Collins, Steve C. (Zootaxa, 2021)
A number of mislabelled butterfly specimens in the Suffert collection purporting to be from Lindi in southeast Tanzania belong to taxa restricted to the Usambara Mountains in northeast Tanzania thus suggesting patria falsa. The history of Suffert’s collection and the possible reasons behind this mislabelling event are discussed in more detail. One of the mislabelled specimens, the holotype of Papilio illyris hamatus Joicey & Talbot, 1918 described from Tanzania, is the senior name for Graphium illyris girardeaui Guilbot & Plantrou, 1978, the latter name formally synonymised herein with the former. A brief biography of the little-known Ernst Suffert is presented.